The Role of Social Capital in Handling the Impact of the COVID-19 Pandemic: A Systematic Literature Review - Wahyudi; Vina Salviana Darvina Soedarwo; David Pradhan (Universitas Muhammadiyah Malang, 2022)
This study aims to categorize themes and concepts in the study of the role of social capital in handling the impact of the COVID-19 pandemic. This research is essential because Covid-19 is still a pandemic, and one way to deal with it is through optimizing social capital. This study is a systematic literature review with the primary data source obtained through the Scopus database. Some of the findings in this study are as follows: First, social capital owned by the community encourages solidarity and cooperation to help each other overcome various problems caused by the pandemic. Second, social capital owned by individuals can be a stronghold in verifying various misinformation that is so rampant amid a pandemic. Third, social capital by parents and families can be a problem-solving in overcoming physical and psychological health problems presented by the COVID-19 pandemic in the closest sphere. Finally, the fourth relates to the role of relevant stakeholders in responding to the impact of the COVID-19 pandemic, primarily through various regulatory packages and efforts that can be carried out linearly in their fields. This research contributes because it shows the urgency and role of social capital in handling COVID-19. The limitation lies in the article's source, which only comes from the Scopus database, so it does not have comparative data and analysis. Therefore, future studies may include other reputable international journal index sources such as the Web of Science (WoS) so that the analysis is broader, comparative, and comprehensive.